Congelamento de sêmen e sua eficiência na inseminação artificial de cães - Chirinea, Viviane Helena [UNESP]; Sicherle, Carmem Cecilia [UNESP]; Lopes, Maria Denise [UNESP] (My University, 2013)
The canine reproductive physiology and unsatisfactory results on techniques of frozen dog semen has been the biggest barrier on the improvement of artificial insemination in dogs. Many researches are been done in this area generating a lot of information, especially on semen technology. The aim of this text is to discuss the major advances on semen evaluation and semen frozen and its influence on artificial insemination results.

A fisiologia reprodutiva da espécie canina e a resposta insatisfatória do sêmen do cão à técnica da congelação são os dois maiores empecilhos aos esforços para o avanço da inseminação artificial em cães. Inúmeras pesquisas estão sendo desenvolvidas nessa área, gerando muitas informações, sobretudo na tecnologia de sêmen. O objetivo desse texto é discutir os principais avanços na avaliação e congelação de sêmen e sua influencia nos resultados de inseminação artificial.
Semen freezing and its efficiency in the artificial insemination in dog
Keywords: Artificial insemination; Semen frozen; Dogs; Inseminação artificial; Congelação de sêmen; Cães